Bio-inspired structures in AM industry - Toivonen, Miko (My University, 2024)
Additive manufacturing (AM) involves production by building objects layer by layer, minimizing waste and enabling the creation of complex geometries. This thesis explores the integration of bio-inspired structures and designs into AM. Bio-inspiration draws inspiration from the structures and mechanisms observed in nature. These structures are studied for their material efficiency and superior mechanical properties such as high strength to weight ratio and lightweight characteristics. The thesis has been done as a literature review of bio-inspired designs, their application in current AM technologies and the challenges and opportunities they present. All sources were found using utuvolter, google scholar and scopus, which are academic search engines. Notably, the thesis investigates the differences of a select few bio-inspired structures, the advantages of AM in their production and their applications across aerospace, automotive, and maritime industries. Bio-inspired designs in AM enhance mechanical properties, enabling the cost-effective production of complex parts with superior strength-to-weight ratios, ideal for aerospace, automotive, and maritime industries. However, challenges such as complex geometric modelling of bio-inspired structures need to be further studied. Future research could focus on improving design and modelling softwares and exploring the limits of currently utilized methods of AM to overcome current limitations.